571 Construction of occupational health nursing diagnosis system for group and organisation in mental health in japan. (24th April 2018) - Yamaguchi, Y; Ito, M; Akimoto, F; Hara, K; Masuzawa, K; Ito, M; Nakamur, H; Yanai, M; Murakami, xxx; Nagano, A; Seto, M; Yoshida, R; et al.
Abstract : Introduction: In order to conduct effective occupational health nursing (OHN) services to groups and organisations, it is necessary to do assessment, planning, implementation and evaluation in line with the nursing process continuously. For that, systematisation of OHN diagnosis is necessary so that the three processes of planning (nursing diagnosis, nursing goal, nursing care) can be systematically utilised in particular. The purpose of this study is to develop OHN diagnosis (diagnostic index, related factor), nursing goal, nursing care in the mental health for groups and organisations, taking 'chronic high stress state' as an example. Methods: Development was advanced by 7 OHN researchers and 10 OHN practitioners, receiving supervision, referring NANDA-I nursing diagnosis and Arizona University NIC. 'Chronic high stress state' which is one of nursing diagnosis in mental health in OHN, an OHN science system was constructed in a format systematically showing three processes. Result: In the nursing diagnosis name 'chronic high stress state', examples of diagnostic indicators were the bad results in stress survey at workplace and the number of workers on leave due to mental disorders, Examples of relevant factors are the qualitative burden of work, the quantitative burden of work. In addition, the nursing goal showed that mental health disorder decreased, new incidences of mental health disorder decreased, nursing care showed recommendations to managers, recommendations to health and safety committee, and so on. Discussion: By systematically arranging the three processes of 'chronic high stress state', the problems of group and organisation (nursing diagnosis and diagnostic index) and its factors (related factor), targeted form (nursing goal), appropriate nursing support, these relationships became clear. In addition, 'Chronic High Stress Condition' is considered to be the basis for constructing a highly versatile system with high support needs in the development of OHN diagnostic system in mental health.